PENGEMBANGAN MODEL LATIHAN TEKNIK DASAR SHOOTING PERMAINAN SEPAKBOLA USIA 12-15 TAHUN PADA PESERTA KEGIATAN EKSTRAKURIKULER SMP - Putra, Eska Pradana; Saichudin, Saichudin; Sudjana, I Nengah (Jurnal Sport Science, 2014)
Abstract :Development Model Basic Training Soccer Game Shooting of Age 12-15 Years on Participants Junior High School Extracurricular Activities.This research aims at developing a model training basic techniques of shooting football games, aged 12-15 years. The subject of the research were students joining extracurricular in Junior High School 1 Blitar. The study used research and development design by Gall and Borg that was adapted into: 1) determining the potential and the problems of research; 2) collecting the information: (a) examining the references, (b) needs analysis; 3) designing products; 4) designing validation, testing football experts (2); 5) improving or revising design; 6) trials phase I (small groups of 6 people); 7 revising II); 8) phase II trial (a large group of 24 persons); 9) final product development. The descriptive analysis was used tp analyze the data. Expert evaluation of football on the results of the needs analysis to testing is 90%, the test results of the phase I tryout for small groups obtained 84.16%, test results for phase II field tryout retrieved results 89.58%. It showed the development of this model was appropriate. The evaluation of media experts obtained 90%, so this shooting exercise model book is appropriate to be used.Keywords :development,  training models, shooting, football games.Abstrak :Penelitian ini bertujuan mengembangkan model latihan teknik dasar shooting permainan sepakbola usia 12-15 tahun dengan subyek penelitian peserta kegiatan ekstrakurikuler di Sekolah Menengah Pertama Negeri (SMPN) 1 Kota Blitar. Metode peneli-tian dan pengembangan menggunakan model pengembangan Borg dan Gall yang di adap-tasi menjadi: 1) menentukan potensi dan masalah penelitian; 2) mengumpulkan informasi:(a)mengkaji  bahanpustaka,  (b)  analisis  kebutuhan;  3)  mendesain  produk;  4)  validasidesain,uji ahli sepakbola (2 orang); 5)perbaikan atau revisi desain; 6) ujicoba tahap I (kelompok kecil 6 orang); 7) revisi II; 8) ujicoba tahap II (kelompok besar sejumlah 24 orang); 9) produk akhir pengembangan. Analisis data yang digunakan adalah analisis deskriptif. Darievaluasi ahli sepakbola terhadap hasil analisis kebutuhan sampai dengan uji coba adalah 90 %, hasil uji tahap I untuk uji kelompok kecil diperoleh hasil 84,16%, dan dari hasil uji tahap II untuk uji coba lapangan diperoleh hasil 89,58%, sehingga pengembangan model latihanshooting ini sangat layak digunakan, sedangkan evaluasi ahli media, diperoleh hasil 90 %, sehingga buku model latihan shooting ini sangat layak digunakan.Kata kunci :pengembangan,  model latihan, shooting, permainan sepakbola.